Method for preparing foamed ceramics at low temperature using waste concrete recycled powder and oil-based drilling cuttings ash
By adopting polyurethane sponge templates in the foamed ceramic preparation process, optimizing the combination of foaming agent and sodium borate, introducing low-melting point solid waste materials, and adopting secondary sintering system and multi-temperature sintering system, the sintering temperature is successfully reduced, the problems of high energy consumption and high cost are solved, and the resource utilization rate of waste is improved, and an environmentally friendly, energy-saving and low-cost production process is realized.
Patent Information
- Application Number
- CN202411016167.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-07-27
AI Technical Summary
The existing foamed ceramic preparation process has high sintering temperature, which leads to high energy consumption and high cost, and the resource utilization of oil-based drill cutting ash slag and waste concrete recycled powder is low, causing environmental pollution.
Polyurethane sponge is used as a template to introduce low-melting point solid waste materials by optimizing the combination of foaming agent and sodium borate, and a secondary sintering system and a multi-temperature sintering system are used to prepare foamed ceramics under low temperature conditions (about 600℃).
It significantly reduces the sintering temperature, solves the problems of high energy consumption and high cost, and improves the resource utilization rate of waste, achieving environmentally friendly, energy-saving and low-cost production processes.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foamed ceramics, in particular to a method for preparing foamed ceramics at low temperature by utilizing waste concrete recycled powder and oil-based drill cuttings ash. Background Art
[0002] Foamed ceramics are a new type of functional material that forms a porous structure by introducing bubbles into a ceramic matrix. As a new type of green building material, it not only has the corrosion resistance and high temperature resistance of ordinary ceramics, but also has good thermal insulation properties, high mechanical strength, good freeze-thaw resistance and other properties. Its performance advantages are more prominent than most green building materials, and it has a wide range of applications. It has been widely used in construction, environmental protection, energy and other fields.
[0003] The raw materials of foamed ceramics are mainly composed of aluminum-silicon raw materials, flux raw materials and foaming agents. However, due to the low quality requirements of raw materials, the preparation of foamed ceramics with solid waste has become the main research direction. Because the use of industrial solid waste as raw materials to produce foamed ceramic materials not only helps to achieve the comprehensive utilization of industrial waste, promote energy conservation and emission reduction, but also reduces enterprise costs. For example, the invention patent CN112811923B discloses a method for preparing high-strength foamed ceramics using solid waste, using industrial solid waste such as coal-based solid waste and metal tailings as the main raw materials, chromium-containing sludge as a crystal phase regulator, adding 0.1-1.0% of a composite foaming agent and 0.05-0.6% of a dispersant, mixing by dry ball milling to form a uniform powder, and then adding 0.5-5% of chopped fibers as a reinforcing agent, and then stirring by wet high-speed to form a uniformly dispersed slurry, and then drying and powdering, mold firing, cooling crystallization, cutting and molding to prepare. Invention patent CN112209734A discloses a method for preparing foamed ceramic materials completely using industrial solid waste, including the following steps: drying and screening industrial solid waste such as fly ash, coal gangue, tailings, polishing slag, etc., mixing various solid wastes by weight ratio by ball milling, spray granulation by spray tower, obtaining granular raw materials, uniformly spreading the sprayed granulated foamed ceramic raw materials on the shed, and placing the foamed ceramic raw materials in a kiln for firing. Invention patent CN105272342B discloses a foamed ceramic thermal insulation board and its preparation method, including the following raw materials in weight percentage: 30% to 60% of waste drilling mud, 10% to 30% of siliceous raw materials, 1% to 10% of clay, 10% to 30% of high-temperature flux, and 0.05% to 10% of foaming agent. However, the calcination temperature used in the preparation of foamed ceramics with qualified performance is generally above 1100℃. The high calcination temperature not only increases energy consumption and production costs, but also puts higher requirements on equipment and processes. Excessive energy consumption restricts the promotion and application of foamed ceramics. Therefore, the development of a new technology that can effectively reduce the sintering temperature of foamed ceramics while ensuring its various properties has important practical significance and broad application prospects.
[0004] During the drilling process of oil and gas field exploration and exploitation, drilling fluid needs to be injected to lubricate and cool the drill bit, build a wall to prevent leakage, and carry rock debris back to the ground. According to the different dispersion media, drilling fluid can be divided into three categories: water-based, synthetic-based and oil-based, to cope with different drilling depths and geological conditions. Oil-based drilling fluid can reduce the shedding of rock cuttings and produce less cuttings, so it has a wider application in drilling. At present, most shale gas wells in China use oil-based drilling fluid, but it has a relatively large environmental impact, which produces solid waste formed by the adhesion of oil-based drilling fluid and rock debris, namely oil-based cuttings. Oil-based cuttings are an oil-containing solid pollutant composed of petroleum, water and cuttings produced during shale gas drilling. Due to its large property changes and complex composition, it is very harmful to the environment. Usually, the ash obtained after heating and degreasing the oil-based cuttings is discarded or used as a low-end inorganic filler. If it cannot be properly disposed of, it will still cause great pollution, but there are few reports on the resource utilization of oil-based cuttings ash. After the waste concrete is crushed and screened, generally only useful recycled coarse aggregate and recycled fine aggregate are collected for the production and preparation of recycled concrete. The chemical components of waste concrete recycled powder are mainly CaO, SiO2 and CaCO3. Due to its low activity and low strength, it is not easy to promote and apply, and is often discarded without being utilized. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is: how to provide a method for preparing foamed ceramics at low temperature using waste concrete recycled powder and oil-based drill cuttings ash, so as to solve the problems commonly existing in the existing preparation process, such as high sintering temperature, high energy consumption, high cost, environmental pollution caused by large accumulation of oil-based drill cuttings ash and waste concrete recycled powder, and low utilization of high value-added resources.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing foamed ceramics at low temperature using waste concrete recycled powder and oil-based drill cuttings ash, comprising the following steps:
[0007] S1: The polyurethane sponge is completely immersed in the sodium borate solution to ensure that the sodium borate solution fully penetrates into the pore structure of the sponge, and then dried to evaporate the water in the sponge to obtain a sodium borate sponge; in this way, the sodium borate sponge is prepared by infiltration, the sodium borate is combined with the sponge material, and the fluxing properties of the sodium borate are used to achieve subsequent low-temperature sintering.
[0008] S2: Mix waste concrete recycled powder, phosphogypsum and oil-based drill cuttings ash to obtain the first powder, and then add polyvinyl alcohol aqueous solution to obtain a uniform and fluid slurry; in this way, waste concrete recycled powder with low melting point is used as the main raw material of the foamed ceramic matrix, in which more CaO can play the role of filling the pores of the matrix. At the same time, the main component of waste concrete recycled powder is calcium carbonate, which has a low decomposition temperature and has begun to decompose at 600°C, and can also play the role of fluxing and foaming at the same time. Phosphogypsum and oil-based drill cuttings ash mainly provide the matrix of foamed ceramics and enhance strength. The addition of waste concrete recycled powder and sodium borate can synergistically reduce the melting point of phosphogypsum and oil-based drill cuttings ash. In addition, the addition of polyvinyl alcohol PVA can improve the flow viscosity of the slurry to a certain extent, so that the solid waste-based materials can adhere well together, while providing initial structural support.
[0009] S3: placing the sodium borate sponge obtained in step S1 into the slurry prepared in step S2, allowing the slurry to completely infiltrate the skeleton and vibrate, allowing the slurry to fully enter the sponge interconnecting holes, and then drying at room temperature to solidify the slurry, and then subjecting it to a first low-temperature sintering treatment. After the reaction is completed, it is naturally cooled, and after grinding and cutting, a foamed ceramic skeleton is obtained; in this way, the obtained skeleton has extremely high porosity and open pores, so that the second sintering slurry material can enter the interior.
[0010] S4: waste concrete recycled powder, phosphogypsum and oil-based drill cuttings ash are mixed to obtain a second powder, and then a foaming agent and sodium borate are added for homogenization and ball milling, and then glycerol is added to obtain a slurry with high fluidity; in this way, the addition of glycerol can improve the fluidity of the slurry, so that the foamed ceramic matrix can be evenly filled in the prepared mold, and at the same time, the decomposition temperature of glycerol is about 280°C, and CO2 and H2O will be produced after decomposition, which can promote the foaming effect in the second sintering process.
[0011] S5: Place the foamed ceramic skeleton obtained in step S3 into the slurry prepared in step S4, so that the slurry completely infiltrates the skeleton and vibrates, so that the slurry fully enters the skeleton interconnecting holes, and then dries at room temperature to solidify the slurry, and then performs a second low-temperature sintering treatment. After the reaction is completed, it is naturally cooled to obtain the foamed ceramic material. In this way, the sodium borate evenly distributed on the sponge structure encounters a liquid phase when the slurry enters the sponge and dissolves in the matrix again, achieving uniform distribution in the matrix, which is beneficial to reducing the second sintering temperature. The area that is not filled with the slurry after the first sintering becomes a residual hole, and the area that is filled with the slurry again undergoes a second sintering, and is foamed by the foaming agent to improve the overall performance of the foamed ceramic.
[0012] Preferably, the sodium borate solution is prepared by the following method: slowly adding water to sodium borate, heating to 60° C. to 80° C., and continuously stirring until the sodium borate is completely dissolved to obtain a uniform saturated solution, that is, the sodium borate solution.
[0013] Preferably, the first powder comprises the following raw materials in parts by weight: 20 to 35 parts of waste concrete recycled powder, 30 to 55 parts of phosphogypsum and 10 to 25 parts of oil-based drill cuttings ash.
[0014] Preferably, the first low-temperature sintering treatment refers to heating the temperature to 275-325°C at a heating rate of 5-10°C / min and keeping it warm for 0.5-1h, and then heating the temperature to 575-625°C at a heating rate of 5-10°C / min and keeping it warm for 0.5-1h; in this way, under heating in the first temperature section, the sponge is partially decomposed at high temperature, and after the sponge is melted and decomposed, the sodium borate precipitate attached to the sponge is evenly retained on the powder matrix; further, under heating in the second temperature section, the sodium borate remaining on the powder matrix promotes the melting of the powder matrix to achieve low-temperature sintering.
[0015] Preferably, the second powder comprises the following raw materials in parts by weight: 5 to 15 parts of waste concrete recycled powder, 30 to 55 parts of phosphogypsum and 10 to 25 parts of oil-based drill cuttings ash.
[0016] Preferably, the second low-temperature sintering treatment refers to heating the temperature to 125-175°C at a heating rate of 5-10°C / min and keeping the temperature for 0.5-1h, then heating the temperature to 275-325°C at a heating rate of 5-10°C / min and keeping the temperature for 0.5-1h, and then heating the temperature to 575-625°C at a heating rate of 5-10°C / min and keeping the temperature for 0.5-1h. Since the foamed ceramic skeleton obtained by the first sintering has more interconnecting holes and open holes, but has a honeycomb network structure, which limits its application, it is further used as a supporting structure for secondary sintering, and combined with a variety of mixed foaming agents, so that the matrix can produce foaming in different low temperature sections, thereby improving the overall performance of the foamed ceramic.
[0017] Preferably, the foaming agent is composed of sodium bicarbonate, sodium peroxide and foam glass powder; in this way, the decomposition temperature of the foaming agent sodium bicarbonate is about 50-200°C, the decomposition temperature of sodium peroxide is about 250-300°C, and the decomposition temperature of the foam glass powder is about 500-800°C. The foaming agent is prepared by mixing three materials with different decomposition temperatures, and a large number of bubbles can be generated in different low temperature ranges. Among them, sodium bicarbonate and sodium peroxide will produce alkali metal oxides when they decompose at high temperature to produce bubbles, and the alkali metal oxides can also play a role of flux in the matrix.
[0018] Preferably, the mass ratio of the sodium bicarbonate, sodium peroxide and foam glass powder is 1-5:1-5:1-5.
[0019] Preferably, the amount of the foaming agent is 5%-10% of the mass of the second powder, and the amount of the sodium borate is 25%-30% of the mass of the second powder.
[0020] Another object of the present invention is to provide a foamed ceramic material prepared by the above method.
[0021] Another object of the present invention is to provide an application of the above foamed ceramic material in the preparation of building thermal insulation decorative panels.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention uses polyurethane sponge as a template, optimizes the combination of foaming agent and sodium borate, introduces low-melting-point solid waste materials, and builds a secondary sintering system and a multi-temperature sintering system. It can prepare foamed ceramic products at a low temperature of about 600°C. This temperature is significantly lower than the conventional foamed ceramic preparation temperature on the market, and achieves low-temperature sintering of foamed ceramics, solving the problems of high sintering temperature, high energy consumption, and high cost that are common in existing preparation processes. The present invention does not introduce toxic or environmentally polluting chemicals, which is cost-saving, safe and environmentally friendly, with a simple process and a short production cycle. This preparation method can not only significantly reduce production costs and energy consumption, but also improve production efficiency and material properties, ensure the thermal insulation performance of foamed ceramics, and promote the application of foamed ceramics in a wider range of fields.
[0024] 2. The porosity of the foamed ceramic prepared by the present invention is 79.94-84.67%, the thermal conductivity is 0.185-0.452W / (m·K), the compressive strength is 3.23-5.69MPa, the water absorption is 4.35-6.08%, and the acid and alkali resistance is more than 98%, which meets the requirements of thermal insulation materials. The present invention has the characteristics of energy saving, environmental protection and emission reduction in the production process, and has the advantages of high strength, low thermal conductivity, corrosion resistance, waterproofness, good processability, etc. It can integrate decorative and thermal insulation properties, and can be widely used as thermal insulation decorative panels for building walls.
[0025] 3. The foamed ceramics prepared by the present invention use waste concrete recycled powder, phosphogypsum and oil-based drill cuttings ash as main raw materials, which can not only improve the resource utilization rate of waste, but also significantly reduce production costs and energy consumption, provide a new solution for industrial solid waste, improve its utilization rate, and realize the efficient resource utilization of traditional industrial waste, turning waste into treasure. Among them, the amount of waste concrete recycled powder and oil-based drill cuttings ash added is relatively large, which not only solves the problems of environmental pollution and harm to human health caused by random stacking, but also provides a high value-added method for the comprehensive utilization of waste concrete recycled powder and oil-based drill cuttings ash, which can achieve huge social and economic benefits. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with examples. It should be understood that the following examples are only exemplary descriptions and explanations of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by known methods.
[0027] Example 1
[0028] A process for preparing foamed ceramic materials at low temperature using solid industrial waste, comprising the following steps, wherein the following raw materials are used in parts by weight:
[0029] S1: Weigh 30 parts of sodium borate, pour it into a stirring device and slowly add water thereto, heat it to 60°C, until the added water can completely dissolve the sodium borate to form a uniform saturated solution, and obtain a sodium borate solution; then cut the polyurethane sponge into a suitable size, completely immerse it in the sodium borate solution, let it stand for about 2 hours to ensure that the sodium borate solution fully penetrates into the pore structure of the sponge, and then place it in a drying oven at a temperature of 100°C for 24 hours to ensure that the water inside the sponge is completely evaporated, leaving the sodium borate deposited in the pores of the sponge, and obtain a sodium borate sponge.
[0030] S2: Weigh solid waste materials according to weight: 30 parts of waste concrete recycled powder, 50 parts of phosphogypsum and 20 parts of oil-based drill cuttings ash, and mix them to obtain a first powder; add water to polyvinyl alcohol (3% of the mass of the first powder) and heat it to 90°C, stirring continuously until the PVA is completely dissolved to obtain a PVA solution; then place the first powder in the PVA solution, stir evenly, and obtain a uniform and fluid slurry.
[0031] S3: placing the sodium borate sponge obtained in step S1 into the slurry prepared in step S2, allowing the slurry to completely infiltrate the sponge and vibrate to allow the slurry to fully enter the sponge interconnecting holes, then drying at room temperature for 24 hours to solidify the slurry, and then subjecting it to the first low-temperature sintering treatment, heating it to 300°C at a heating rate of 5°C / min and keeping it warm for 0.5h, and then heating it to 600°C at a heating rate of 5°C / min and keeping it warm for 1h. After the reaction is completed, it is naturally cooled, and after grinding and cutting, a foamed ceramic skeleton is obtained.
[0032] S4: Weigh the solid waste materials according to their weight: 5 parts of recycled concrete powder, 50 parts of phosphogypsum, and 20 parts of oil-based drill cuttings ash, mix them to obtain the second powder, then add 5 parts of foaming agent (the mass ratio of sodium bicarbonate, sodium peroxide and foam glass powder is 3:3:4) and 20 parts of sodium borate to carry out homogenization treatment and grind them together in a ball mill for 1 hour to allow the raw materials to be fully mixed and reacted to obtain a dry slurry, and then add an appropriate amount of glycerin to obtain a slurry with high fluidity.
[0033] S5: placing the foamed ceramic skeleton obtained in step S3 into the slurry prepared in step S4, allowing the slurry to completely infiltrate the skeleton and vibrate through a vibration table to allow the slurry to fully enter the connecting holes of the skeleton, then drying at room temperature for 48 hours to solidify the slurry, and then subjecting it to a second low-temperature sintering treatment, heating it to 150°C at a heating rate of 10°C / min and keeping it warm for 0.5h, then heating it to 300°C at a heating rate of 10°C / min and keeping it warm for 0.5h, then heating it to 600°C at a heating rate of 10°C / min and keeping it warm for 0.5h. After the reaction is completed, it is naturally cooled to obtain the foamed ceramic material.
[0034] Example 2
[0035] A process for preparing foamed ceramic materials at low temperature using solid industrial waste, comprising the following steps, wherein the following raw materials are used in parts by weight:
[0036] S1: Weigh 30 parts of sodium borate, pour it into a stirring device and slowly add water thereto, heat it to 60°C, until the added water can completely dissolve the sodium borate to form a uniform saturated solution, and obtain a sodium borate solution; then cut the polyurethane sponge into a suitable size, completely immerse it in the sodium borate solution, let it stand for about 2 hours to ensure that the sodium borate solution fully penetrates into the pore structure of the sponge, and then place it in a drying oven at a temperature of 100°C for 24 hours to ensure that the water inside the sponge is completely evaporated, leaving the sodium borate deposited in the pores of the sponge, and obtain a sodium borate sponge.
[0037] S2: Weigh solid waste materials according to weight: 30 parts of waste concrete recycled powder, 50 parts of phosphogypsum and 20 parts of oil-based drill cuttings ash, and mix them to obtain a first powder; add water to polyvinyl alcohol (3% of the mass of the first powder) and heat it to 90°C, stirring continuously until the PVA is completely dissolved to obtain a PVA solution; then place the first powder in the PVA solution, stir evenly, and obtain a uniform and fluid slurry.
[0038] S3: Place the sodium borate sponge obtained in step S1 into the slurry prepared in step S2, allow the slurry to completely soak the skeleton and vibrate to allow the slurry to fully enter the sponge interconnecting holes, then dry at room temperature for 24 hours to solidify the slurry, and then perform the first low-temperature sintering treatment, heating the temperature to 300°C at a heating rate of 5°C / min and keeping it warm for 0.5h, then heating the temperature to 600°C at a heating rate of 5°C / min and keeping it warm for 1h. After the reaction is completed, cool naturally, and obtain a foamed ceramic skeleton after grinding and cutting.
[0039] S4: Weigh the solid waste materials according to their weight: 10 parts of recycled concrete powder, 30 parts of phosphogypsum, and 15 parts of oil-based drill cuttings ash, mix them to obtain the second powder, then add 5 parts of foaming agent (the mass ratio of sodium bicarbonate, sodium peroxide and foam glass powder is 3:3:4) and 15 parts of sodium borate to carry out homogenization treatment and grind them together in a ball mill for 1 hour to allow the raw materials to be fully mixed and reacted to obtain a dry slurry, and then add an appropriate amount of glycerin to obtain a slurry with high fluidity.
[0040] S5: placing the foamed ceramic skeleton obtained in step S3 into the slurry prepared in step S4, allowing the slurry to completely infiltrate the skeleton and vibrate through a vibration table to allow the slurry to fully enter the connecting holes of the skeleton, then drying at room temperature for 48 hours to solidify the slurry, and then subjecting it to a second low-temperature sintering treatment, heating the temperature to 150°C at a heating rate of 10°C / min and keeping it warm for 0.5h, then heating the temperature to 300°C at a heating rate of 10°C / min and keeping it warm for 0.5h, and then heating the temperature to 600°C at a heating rate of 10°C / min and keeping it warm for 0.5h. After the reaction is completed, naturally cool it to obtain the foamed ceramic material.
[0041] Example 3
[0042] A process for preparing foamed ceramic materials at low temperature using solid industrial waste, comprising the following steps, wherein the following raw materials are used in parts by weight:
[0043] S1: Weigh 30 parts of sodium borate, pour it into a stirring device and slowly add water thereto, heat it to 60°C, until the added water can completely dissolve the sodium borate to form a uniform saturated solution, and obtain a sodium borate solution; then cut the polyurethane sponge into a suitable size, completely immerse it in the sodium borate solution, let it stand for about 2 hours to ensure that the sodium borate solution fully penetrates into the pore structure of the sponge, and then place it in a drying oven at a temperature of 100°C for 24 hours to ensure that the water inside the sponge is completely evaporated, leaving the sodium borate deposited in the pores of the sponge, and obtain a sodium borate sponge.
[0044] S2: Weigh solid waste materials according to weight: 35 parts of waste concrete recycled powder, 55 parts of phosphogypsum and 10 parts of oil-based drill cuttings ash, and mix them to obtain a first powder; add water to polyvinyl alcohol (3% of the mass of the first powder) and heat it to 90°C, and stir continuously until the PVA is completely dissolved to obtain a PVA solution; then place the first powder in the PVA solution, stir evenly, and obtain a uniform and fluid slurry.
[0045] S3: Place the sodium borate sponge obtained in step S1 into the slurry prepared in step S2, allow the slurry to completely infiltrate the skeleton and vibrate to allow the slurry to fully enter the sponge interconnecting holes, then dry at room temperature for 24 hours to solidify the slurry, and then perform the first low-temperature sintering treatment, heating the temperature to 300°C at a heating rate of 5°C / min and keeping it warm for 0.5h, then heating the temperature to 600°C at a heating rate of 5°C / min and keeping it warm for 1h. After the reaction is completed, cool naturally, and obtain a foamed ceramic skeleton after grinding and cutting.
[0046] S4: Weigh low-melting-point solid waste materials according to weight proportions: 5 parts of recycled concrete powder, 50 parts of phosphogypsum, and 20 parts of oil-based drill cuttings ash, mix them to obtain a second powder, then add 5 parts of a foaming agent (the mass ratio of sodium bicarbonate, sodium peroxide and foam glass powder is 3:3:4) and 20 parts of borax for homogenization and grind them together in a ball mill for 1 hour to allow the raw materials to be fully mixed and reacted to obtain a dry slurry, and then add an appropriate amount of glycerin to obtain a slurry with high fluidity.
[0047] S5: placing the foamed ceramic basic skeleton obtained in step S3 into the slurry prepared in step S4, allowing the slurry to completely infiltrate the skeleton and vibrate through a vibration table to allow the slurry to fully enter the skeleton's connecting holes, then drying at room temperature for 48 hours to solidify the slurry, and then subjecting it to a second low-temperature sintering treatment, heating the temperature to 150°C at a heating rate of 10°C / min and keeping it warm for 0.5h, then heating the temperature to 300°C at a heating rate of 10°C / min and keeping it warm for 0.5h, and then heating the temperature to 600°C at a heating rate of 10°C / min and keeping it warm for 0.5h. After the reaction is completed, it is naturally cooled to obtain the foamed ceramic material.
[0048] Example 4
[0049] A process for preparing foamed ceramic materials at low temperature using solid industrial waste, comprising the following steps, wherein the following raw materials are used in parts by weight:
[0050] S1: Weigh 30 parts of sodium borate, pour it into a stirring device and slowly add water thereto, heat it to 60°C, until the added water can completely dissolve the sodium borate to form a uniform saturated solution, and obtain a sodium borate solution; then cut the polyurethane sponge into a suitable size, completely immerse it in the sodium borate solution, let it stand for about 2 hours to ensure that the sodium borate solution fully penetrates into the pore structure of the sponge, and then place it in a drying oven at a temperature of 100°C for 24 hours to ensure that the water inside the sponge is completely evaporated, leaving the sodium borate deposited in the pores of the sponge, and obtain a sodium borate sponge.
[0051] S2: Weigh solid waste materials according to weight: 35 parts of waste concrete recycled powder, 55 parts of phosphogypsum and 10 parts of oil-based drill cuttings ash, and mix them to obtain a first powder; add water to polyvinyl alcohol (3% of the mass of the first powder) and heat it to 90°C, and stir continuously until the PVA is completely dissolved to obtain a PVA solution; then place the first powder in the PVA solution, stir evenly, and obtain a uniform and fluid slurry.
[0052] S3: Place the sodium borate sponge obtained in step S1 into the slurry prepared in step S2, allow the slurry to completely infiltrate the skeleton and vibrate to allow the slurry to fully enter the sponge interconnecting holes, then dry at room temperature for 24 hours to solidify the slurry, and then perform the first low-temperature sintering treatment, heating the temperature to 300°C at a heating rate of 5°C / min and keeping it warm for 0.5h, then heating the temperature to 600°C at a heating rate of 5°C / min and keeping it warm for 1h. After the reaction is completed, cool naturally, and obtain a foamed ceramic skeleton after grinding and cutting.
[0053] S4: Weigh low-melting-point solid waste materials according to weight proportions: 5 parts of recycled concrete powder, 50 parts of phosphogypsum, and 20 parts of oil-based drill cuttings ash, mix them to obtain a second powder, then add 5 parts of a foaming agent (the mass ratio of sodium bicarbonate, sodium peroxide and foam glass powder is 4:3:3) and 20 parts of borax for homogenization and grind them together in a ball mill for 1 hour to allow the raw materials to be fully mixed and reacted to obtain a dry slurry, and then add an appropriate amount of glycerin to obtain a slurry with high fluidity.
[0054] S5: placing the foamed ceramic skeleton obtained in step S3 into the slurry prepared in step S4, allowing the slurry to completely infiltrate the skeleton and vibrate through a vibration table to allow the slurry to fully enter the connecting holes of the skeleton, then drying at room temperature for 48 hours to solidify the slurry, and then subjecting it to a second low-temperature sintering treatment, heating it to 150°C at a heating rate of 10°C / min and keeping it warm for 0.5h, then heating it to 300°C at a heating rate of 10°C / min and keeping it warm for 0.5h, then heating it to 600°C at a heating rate of 10°C / min and keeping it warm for 0.5h. After the reaction is completed, it is naturally cooled to obtain the foamed ceramic material.
[0055] Example 5
[0056] A process for preparing foamed ceramic materials at low temperature using solid industrial waste, comprising the following steps, wherein the following raw materials are used in parts by weight:
[0057] S1: Weigh 30 parts of sodium borate, pour it into a stirring device and slowly add water thereto, heat it to 60°C, until the added water can completely dissolve the sodium borate to form a uniform saturated solution, and obtain a sodium borate solution; then cut the polyurethane sponge into a suitable size, completely immerse it in the sodium borate solution, let it stand for about 2 hours to ensure that the sodium borate solution fully penetrates into the pore structure of the sponge, and then place it in a drying oven at a temperature of 100°C for 24 hours to ensure that the water inside the sponge is completely evaporated, leaving the sodium borate deposited in the pores of the sponge, and obtain a sodium borate sponge.
[0058] S2: Weigh solid waste materials according to weight: 30 parts of waste concrete recycled powder, 50 parts of phosphogypsum and 20 parts of oil-based drill cuttings ash, and mix them to obtain a first powder; add water to polyvinyl alcohol (3% of the mass of the first powder) and heat it to 90°C, stirring continuously until the PVA is completely dissolved to obtain a PVA solution; then place the first powder in the PVA solution, stir evenly, and obtain a uniform and fluid slurry.
[0059] S3: Place the sodium borate sponge obtained in step S1 into the slurry prepared in step S2, allow the slurry to completely infiltrate the skeleton and vibrate to allow the slurry to fully enter the sponge interconnecting holes, then dry at room temperature for 24 hours to solidify the slurry, and then perform the first low-temperature sintering treatment, heating the temperature to 350°C at a heating rate of 10°C / min and keeping it warm for 0.5h, and then heating the temperature to 600°C at a heating rate of 10°C / min and keeping it warm for 1h. After the reaction is completed, cool naturally, and obtain a foamed ceramic skeleton after grinding and cutting.
[0060] S4: Weigh low-melting-point solid waste materials according to weight proportions: 5 parts of recycled concrete powder, 50 parts of phosphogypsum, and 20 parts of oil-based drill cuttings ash, mix them to obtain a second powder, then add 5 parts of a foaming agent (the mass ratio of sodium bicarbonate, sodium peroxide and foam glass powder is 3:3:4) and 20 parts of borax for homogenization and grind them together in a ball mill for 1 hour to allow the raw materials to be fully mixed and reacted to obtain a dry slurry, and then add an appropriate amount of glycerin to obtain a slurry with high fluidity.
[0061] S5: placing the foamed ceramic basic skeleton obtained in step S3 into the slurry prepared in step S4, allowing the slurry to completely infiltrate the skeleton and vibrate through a vibration table to allow the slurry to fully enter the connecting holes of the skeleton, then drying at room temperature for 48 hours to solidify the slurry, and then subjecting it to a second low-temperature sintering treatment, heating it to 150°C at a heating rate of 8°C / min and keeping it warm for 0.5h, then heating it to 300°C at a heating rate of 8°C / min and keeping it warm for 0.5h, and then heating it to 600°C at a heating rate of 10°C / min and keeping it warm for 0.5h. After the reaction is completed, it is naturally cooled to obtain the foamed ceramic material.
[0062] Comparative Example 1
[0063] No second low-temperature sintering treatment was performed, and other steps were the same as in Example 1.
[0064] Comparative Example 2
[0065] The foaming agent is only sodium bicarbonate, and the other steps are the same as in Example 1.
[0066] The water absorption, acid and alkali resistance, porosity and compressive strength of the foamed ceramic materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were tested respectively. The results are shown in Table 1.
[0067] The water absorption rate of the foamed ceramic sample is determined by referring to the method of GB / T5486-2008 "Test Methods for Inorganic Rigid Insulation Products". The specific steps are: after drying the sample to constant weight, weigh its mass as m1, then soak the sample in water for 2 hours and wipe off the residual water on the surface of the sample with a wet wipe, and then weigh its mass as m2. The water absorption rate of the foamed ceramic can be calculated by formula (1):
[0068]
[0069] In the formula: w represents the water absorption rate of the sample, m1 represents the mass of the sample before water absorption, and m2 represents the mass of the sample after water absorption.
[0070] The acid and alkali resistance of the foamed ceramic sample was tested with reference to GB / T1970-1996 "Test Method for Acid and Alkali Corrosion Resistance of Porous Ceramics". The specific steps are as follows: weigh the mass m0 of the dry sample, place the sample in a beaker, pour the prepared hydrochloric acid and sodium hydroxide solution into the sample, and then seal the mouth of the test tube with a plastic film to prevent the concentration of the acid solution from changing; after soaking for a certain period of time, take out the sample, dry it, and weigh its mass m a The acid and alkali corrosion resistance is expressed by comparing the percentage of mass before and after corrosion test. The acid and alkali resistance of foamed ceramic can be calculated by formula (2):
[0071] R=m a / m0 (2)
[0072] In the formula: R represents acid and alkali resistance %; m a represents the mass g of the sample after corrosion, and m0 represents the mass g of the sample before corrosion.
[0073] The porosity of the foamed ceramic sample was tested with reference to GB / T1967-1996 "Test Method for Properties of Porous Ceramics". The sample volume density and true density were used for calculation. Based on the specific gravity bottle method to test the true density of the sample, the porosity of the foamed ceramic can be calculated by formula (3):
[0074]
[0075] Where: P-sample porosity%, ρ-sample volume density, g / cm 3 , ρ0-sample true density g / cm 3 .
[0076] The compressive strength of the foamed ceramic sample was determined by referring to the method of GB / T5486-2008 "Test methods for inorganic rigid thermal insulation products", which can be calculated by formula (4):
[0077] σ=F / A (4)
[0078] Where: σ represents the compressive strength of the sample MPa, F represents the sample failure load N, and A represents the compressive area of the sample mm 2 .
[0079] Table 1
[0080]
[0081]
[0082] As can be seen from Table 1, compared with the comparative example, the foamed ceramics prepared by the present invention have obvious advantages in compressive strength, porosity and thermal conductivity, with a porosity of 79.94-84.67%, a thermal conductivity of 0.185-0.452 W / (m·K), a compressive strength of 3.23-5.69 MPa, a water absorption of 4.35-6.08%, and an acid-base resistance of more than 98%, which meets the requirements of thermal insulation materials and can be widely used in thermal insulation decorative panels of building walls. It shows that the foamed ceramics prepared by the present invention not only effectively reduce the sintering temperature, but also ensure its excellent performance.
[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing foamed ceramics at low temperature using waste concrete recycled powder and oil-based drill cuttings ash, characterized in that: The following steps are involved: S1: completely immersing the polyurethane sponge in the sodium borate solution to ensure that the sodium borate solution fully penetrates into the pore structure of the sponge, and then drying it to evaporate the water in the sponge to obtain a sodium borate sponge; S2: mixing waste concrete recycled powder, phosphogypsum and oil-based drill cuttings ash to obtain a first powder, and then adding a polyvinyl alcohol aqueous solution to obtain a uniform and fluid slurry; S3: placing the sodium borate sponge obtained in step S1 in the slurry prepared in step S2, so that the slurry completely infiltrates the sodium borate sponge and vibrates, so that the slurry fully enters the interconnecting holes of the sodium borate sponge, and then drying at room temperature to solidify the slurry, and then performing a first low-temperature sintering treatment on it. After the reaction is completed, it is naturally cooled, and after grinding and cutting, a foamed ceramic skeleton is obtained; the first low-temperature sintering treatment refers to heating to 275~325℃ at a heating rate of 5~10℃ / min and keeping warm for 0.5~1h, and then heating to 575~625℃ at a heating rate of 5~10℃ / min and keeping warm for 0.5~1h; S4: mixing the waste concrete recycled powder, phosphogypsum and oil-based drill cuttings ash to obtain a second powder, then adding a foaming agent and sodium borate to perform homogenization treatment and ball milling, and then adding glycerin to obtain a slurry with high fluidity; S5: placing the foamed ceramic skeleton obtained in step S3 into the slurry prepared in step S4, allowing the slurry to completely infiltrate the skeleton and vibrate, allowing the slurry to fully enter the skeleton connecting holes, then drying at room temperature to solidify the slurry, and then subjecting it to a second low-temperature sintering treatment. After the reaction is completed, it is naturally cooled to obtain the foamed ceramic; the second low-temperature sintering treatment refers to heating the temperature to 125~175℃ at a heating rate of 5~10℃ / min and keeping the temperature for 0.5~1h, then heating the temperature to 275~325℃ at a heating rate of 5~10℃ / min and keeping the temperature for 0.5~1h, and then heating the temperature to 575~625℃ at a heating rate of 5~10℃ / min and keeping the temperature for 0.5~1h.
2. The method for preparing foamed ceramics at low temperature by using waste concrete recycled powder and oil-based drill cuttings ash according to claim 1, characterized in that: The sodium borate solution is prepared by the following method: slowly adding water to the sodium borate, heating to 60° C. to 80° C., and continuously stirring until the sodium borate is completely dissolved to obtain a uniform saturated solution, that is, the sodium borate solution.
3. The method for preparing foamed ceramics at low temperature by using waste concrete recycled powder and oil-based drill cuttings ash according to claim 1, characterized in that: The first powder material comprises the following raw materials in parts by weight: 20-35 parts of waste concrete recycled powder, 30-55 parts of phosphogypsum and 10-25 parts of oil-based drill cuttings ash.
4. The method for preparing foamed ceramics at low temperature by using waste concrete recycled powder and oil-based drill cuttings ash according to claim 1, characterized in that: The second powder material comprises the following raw materials in parts by weight: 5-15 parts of waste concrete recycled powder, 30-55 parts of phosphogypsum and 10-25 parts of oil-based drill cuttings ash.
5. The method for preparing foamed ceramics at low temperature by using waste concrete recycled powder and oil-based drill cuttings ash according to claim 1, characterized in that: The foaming agent consists of sodium bicarbonate, sodium peroxide and foam glass powder; the mass ratio of the sodium bicarbonate, sodium peroxide and foam glass powder is 1-5:1-5:1-5.
6. The method for preparing foamed ceramics at low temperature by using waste concrete recycled powder and oil-based drill cuttings ash according to claim 1, characterized in that: In step S4, the amount of the foaming agent used is 5% to 10% of the mass of the second powder, and the amount of the sodium borate used is 25% to 30% of the mass of the second powder.
7. The foamed ceramic material prepared by the method according to any one of claims 1 to 6.
8. Use of the foamed ceramic material as claimed in claim 7 in preparing building thermal insulation decorative panels.
Citation Information
Patent Citations
Foamed ceramic thermal insulation board and its preparation method
CN105272342B
Method for preparing foamed ceramic material by completely utilizing industrial solid wastes
CN112209734A
A method for preparing high-strength foamed ceramics using solid waste
CN112811923B
Quartz porous ceramic material and preparation technology thereof
CN101698594A
Method for preparing non-autoclaved aerated concrete blocks by using oil-based drill cutting residues
CN105967614A